How Symmetric Are the Shocks and the Shock Adjustment Dynamics Between the Euro Area and Central and Eastern European Countries? - Frenkel, Michael (IMF Working Papers; Working Paper ;, 2002)
In this paper, we use a structural vector autoregression model to identify and compare demand and supply shocks between euro area countries and central and eastern European countries (CEECs). The shocks and the shock adjustment dynamics of these countries are also compared to EU countries that currently do not participate in the EMU. Focusing on the period 1993-2001, we find that there are still differences in the shocks and in the adjustment process to shocks between the euro area and the CEECs. However, several individual CEECs exhibit shocks and shock adjustment processes that are fairly similar to some euro area countries.